Relevansi Pendidikan Kritis Paulo Freire Dengan Pendidikan Islam - Muhammad Zamroji (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2016)
Education represent process humanize human being which is plan and is continual. In Islam, education become system sub owning separate urgency in supporting intelectuality dimension and of spiritualitas Islam people. But reality that happened these days, frequently show education face which do not in line with principle of humanization. Education system which have there is and establish during the time can be pledged by as a "bank" (educational of concept banking) where student given by science to be thereof is later expected by an multiple result. Become protege is invesment obyek and source of deposit potential, teacher become active subyek, protege is malleable passive obyek. As strategic step, education world have to reconstruct idea of education. One of them is Paulo Freire which intensively keen criticism to education reality, Freire is famous figure with critical education concept of him, he tread on at principle of humanization the which critical approach represent step early in developing critical natural existence in education as reference think objective and offer one of the method alternative and strategy conception study. By tread on at critical education paradigm, education expected can awaken critical natural existence, creative ability, freedom in apresiation, and critical awareness of educative participant. For that, pattern of paedagogi becoming especial patron used in course of learning to teach at education system during the time have to change with pattern education of more opening andragogi of opportunity to educative participant to participate actively is, critical, and creative in course of learning to teach. Relate at concept education of Islam, basically education of Islam very is emphasizing of liberation and humanization as education orientation, and also place educative participant and educator both of the same as subjek in course of learning to teach. Because, Paradigm education of Islam base entire/all idea, target of, and education process at basis for sturdy belief in God and spiritualitas to Allah and of Rasul-Nya. Or equally education of Islam all vertical aspect (and spiritualitas) of horizontal (sosial) as education orientation. And one of the critical education idea that is creating situation learn democratic, and also create the condition of participant of education shall no longger embrace absolute understanding, normative, which is very kill to educative participant natural existence energy.